(untitled) (Journal of Science and Technology, 2022)
Despite the evidence that an increase in cyberloafing can be unfavourable to firms, workers commonly view cyberloafing to be a no-harm activity and believe it does not have a significant impact on performance in an organisation. This study sought to find out if cyberloafing activi-ties existed among student-workers in organisations in Ghana and how it affects their work. A descriptive survey design was employedfor the study. The study participants were student-workers enrolled in an MBA programme at a University in Ghana. Responses of286 sampledparticipants were usedfor the analyses. The data analysesfor the research questions made use ofmeans and standard deviation. Independence sample t-test was used to test the hypothesis. Results from the study showed that the most cyberloafing activity ofparticipants ofthe study was Instant messaging. The least cyberloafing activity ofparticipants of the study was Online games. The results also indicated that males do more cyberloafing than females although there was nostatistical difference be-tween the sexee. Conclusions drawn from this study have shown that cyberloafing is generally widespread at the office. Organisations need to orient and educate staffon the negative effects ofcyberloafing in order not to waste the company’sproductive time.